Effect of a sudden and a slow concentration increase in plasma urea on its concentration in some tissues of the dog and rat - Heller, J; Kleinová, M; Janácek, K; Rybová, R (Physiologia Bohemoslovaca, 1984)
The urea concentration in the renal cortex ([RC]) of pentobarbital-anaesthetized dogs was 5.71 times higher than the plasma concentration ([P]); the liver ([L]) and the skeletal muscle ([SM]) concentrations were the same as ([P]). Rapid infusion of 20% urea (1 g/kg b.w. within 1 min) was followed by a sudden increase in [P]; [RC] and [L] rose to values nonsignificantly different from [P] and remained non-significantly different for the whole 4 hours of the experiment; at the end, [P] was still about 10 times higher than before infusion. Surprisingly, [SM] 2 and 6 min after infusion was significantly lower than [P]; later they were the same. The experiment thus does not testify to the existence of active transport of urea in the RC. The permeability of the skeletal muscle membrane for urea is lower than that of the RC and liver. Chronic uraemia was induced in rats by transplanting the trigonum vesicae into the peritoneal cavity. In addition to the chemical determination of urea, 14C-urea (marked*) was also measured. [RC]/[P] and [RC*]/[P*] fell as [P] rose; [L], [L*] [SM] and [SM*] never differed from [P] or [P*]. Fluid [PF] collected in the peritoneal cavity had the same chemically determined and radioactive urea concentration as P, but it was hypoosmolar and had a lower [Na+] than P. These experiments likewise did not testify to active urea transport in the RC. It is not clear what caused the osmolarity and sodium gradient between the PF and P, but the peritoneal wall definitely did not act as a simple dialyzing membrane.
Keywords: Muscles; játra; psi; Kidney Cortex; Sodium; Dogs; Urea; svaly; Female; Rats, Inbred Strains; tkáňová distribuce; krysa rodu Rattus; uremie; zvířata; kůra ledviny; osmolární koncentrace; močovina; Kinetics; biologický transport; peritoneum; ženské pohlaví; Liver; Tissue Distribution; Male; sodík; Extracellular Space; Rats; Peritoneum; Animals; mužské pohlaví; Uremia; Osmolar Concentration; kinetika; Biological Transport; inbrední kmeny potkanů; extracelulární prostor